Kaizen Method Implementation in Industries: Literature Review and Research Issues - Muhammad Julian Syaputra; Siti Aisyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
A business philosophy in a corporate organization that involves all elements from the leadership level to workers to contribute to the processes that support an organizational system, such as work and time efficiency, work environment and safety, waste management, production processes and other processes.  Kaizen has been widely accepted by various types of industries, both manufacturing and services, in response to these requirements, because kaizen itself can eliminate waste without additional resource requirements.  This research aims to know and provide information about Kaizen implementation from various types of industries.  This paper uses the literature review method of research papers that generally apply kaizen. A total of 52 research papers have been reviewed as research contributions, type of research methodology adopted, techniques and tools used, type of industry, and year of publication. The results obtained were published in many researchs about kaizen at 2012-2019, Kaizen approach can solve kind of problems such as quality, consumption energy, lead time, performance problem, etc. to improve the work system, widely applied in various industries such as: manufacturing, logistics, construction, SME, service, healthcare, pharmaceutical and processes for continuous improvement.